1999
DOI: 10.1089/10430349950018832
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus as an in Situ Cancer Vaccine for the Induction of Specific Anti-Tumor Immunity

Abstract: The success of cancer gene therapy is likely to require the targeting of multiple antitumor mechanisms. One strategy involves the use of attenuated, replication-competent virus vectors, such as herpes simplex virus type 1 (HSV-1) mutant G207, which is able to replicate in human tumor cells with resultant cell death and tumor growth inhibition, yet is nonpathogenic in normal tissue. In this study, we demonstrate that infection of established tumors with G207 also induces a highly specific systemic anti-tumor im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
200
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 244 publications
(210 citation statements)
references
References 31 publications
10
200
0
Order By: Relevance
“…It is evident that the oncolytic effect of the virus accounts for at least a portion of its anti-tumor effects; other studies suggest that an anti-tumor immune response can also be induced by the virus in animal models. 10,11,21 Safety of G207 has been demonstrated by intracerebral inoculation in naive animals including sensitive mouse strains (BALB/c, A/J strain) and highly susceptible primates (Aotus nancymai). No evidence of encephalitis, either clinically or histologically, has been seen in these animals with G207 doses up to 10 9 p.f.u.…”
Section: Gene Therapymentioning
confidence: 99%
“…It is evident that the oncolytic effect of the virus accounts for at least a portion of its anti-tumor effects; other studies suggest that an anti-tumor immune response can also be induced by the virus in animal models. 10,11,21 Safety of G207 has been demonstrated by intracerebral inoculation in naive animals including sensitive mouse strains (BALB/c, A/J strain) and highly susceptible primates (Aotus nancymai). No evidence of encephalitis, either clinically or histologically, has been seen in these animals with G207 doses up to 10 9 p.f.u.…”
Section: Gene Therapymentioning
confidence: 99%
“…CT26 cells, derived from one of the murine tumors susceptible to G207, are efficiently destroyed by G207 at an MOI of 1 but not 0.1 pfu/cell in vitro. 10 Infection at an MOI of 1 reflects the Figure 6 Involvement of anti -HSV immunity in the significant antitumor effect of the combined treatment. Tumor cells were injected into the brain ( 1Â10 4 CT26 cells ) and skin ( 5Â10 5 P815 cells ) of BALB / c mice ( i.c.…”
Section: Cancer Gene Therapymentioning
confidence: 99%
“…In contrast, in models with bilaterally established syngeneic tumors in immunocompetent mice, G207 inoculation of one tumor inhibited the growth of both the inoculated and the distant, noninoculated tumors. 10 Unlike the situation in athymic mice, tumor growth inhibition in immunocompetent mice involves the induction of an antitumor T-cell response. 10 -13 These observations suggested that treatment of local tumors with G207 affects distant metastatic tumors through the induction of a specific immune response against tumor antigens.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies of oncolytic viruses have been performed on small tumors. We reviewed 16 studies of oncolytic HSVs in non-CNS tumors published between 1998 and 2003, and found that the average tumor size injected in 14 studies was o150 mm 3 , 17,21,[34][35][36][37][38][39][40][41][42][43][44][45] in two studies was 150-250 mm 3 , 46,47 and in no study was 4250 mm 3 . We used a high-risk alveolar rhabomyosarcoma model to determine the effect of oncolytic HSV injections on large human tumor xenografts.…”
mentioning
confidence: 99%